Preparation method and application of perovskite thin film
During the preparation process of perovskite solar cells, the method of using aminoethanesulfonic acid to repair film defects is formed to form a high-quality perovskite film, which solves the problem of low preparation efficiency of the total evaporation method and improves the photoelectric conversion of solar cells Efficiency and manufacturing uniformity.
Patent Information
- Application Number
- CN202411363102.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
The efficiency of existing perovskite solar cells prepared by the full evaporation method is lower than that of the solution method, mainly due to the defects in the perovskite film and the non-radiative recombination limiting the photoelectric conversion efficiency.
The skeleton layer is formed under the solid substrate by the first evaporation treatment, the organic layer is formed by the second evaporation treatment, and annealing is performed, and aminoethanesulfonic acid is used as the evaporation source to repair film defects and improve the quality of the perovskite film.
The open circuit voltage and filling factor of perovskite solar cells are significantly improved, the photoelectric conversion efficiency is improved, and large-area uniform manufacturing is achieved.
Smart Images

Figure CN119277944A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cell technology. Specifically, the present invention relates to a method for preparing a perovskite film and its application. Background Art
[0002] Perovskite materials have advanced optoelectronic properties and simple solution preparation processes. The prepared perovskite solar cells can achieve high-efficiency and low-cost solar power generation. High-quality perovskite films are the key to achieving high-performance photovoltaic devices. So far, perovskite solar cells and perovskite films with high photoelectric conversion efficiency are prepared by solution processing technology. However, the complex chemical properties of perovskite precursor solutions make it difficult to prepare large-area devices in a reproducible manner. Compared with the solution method, the full evaporation method has many advantages, such as high uniformity of large-area preparation, solvent-free, conformal growth of thin films, and higher compatibility with existing photovoltaic production technologies. However, the efficiency of perovskite solar cells prepared by the full evaporation method is still lower than that of the solution method. Among them, defects and non-radiative recombination in the perovskite film are the main reasons limiting its photoelectric conversion efficiency.
[0003] Therefore, it is crucial to prepare high-quality perovskite layers with few defects. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art to at least a certain extent.
[0005] Therefore, in the first aspect of the present application, the present application proposes a method for preparing a perovskite film. According to an embodiment of the present application, the method includes: performing a first evaporation treatment on a first evaporation source below a solid substrate to form a skeleton layer on the lower surface of the solid substrate, wherein the first evaporation source includes aminoethanesulfonic acid; performing a second evaporation treatment on a second evaporation source below the formation of the skeleton layer to form an organic layer on the lower surface of the skeleton layer; annealing the skeleton layer and the organic layer to obtain the perovskite film. By adding aminoethanesulfonic acid as an evaporation source during the preparation of the perovskite film, the defects inside the perovskite film can be effectively repaired, thereby significantly improving the quality of the film. This improvement not only improves the open circuit voltage and fill factor of the perovskite solar cell, but also further improves the photoelectric conversion efficiency of the cell. In addition, the method also helps to achieve uniform manufacturing of large-area perovskite solar cells.
[0006] According to an embodiment of the present invention, the above method for preparing a perovskite film may further include at least one of the following additional technical features:
[0007] According to an embodiment of the present application, the first evaporation source includes a third evaporation source, a fourth evaporation source, and a fifth evaporation source, and the fifth evaporation source includes the aminoethanesulfonic acid.
[0008] According to an embodiment of the present application, the first evaporation treatment includes performing a co-evaporation treatment or a sequential evaporation treatment on the first evaporation source.
[0009] According to an embodiment of the present application, a sequential evaporation treatment is performed on the first evaporation source, and the sequential evaporation treatment includes: performing a third evaporation treatment on the third evaporation source and the fourth evaporation source; and performing a fourth evaporation treatment on the fifth evaporation source.
[0010] According to an embodiment of the present application, the third evaporation source includes lead iodide.
[0011] According to an embodiment of the present application, the fourth evaporation source includes at least one of cesium bromide and cesium iodide.
[0012] According to an embodiment of the present application, during the co-evaporation process, the evaporation rate of the third evaporation source is The evaporation rate of the fourth evaporation source is The evaporation rate of the fifth evaporation source is
[0013] According to an embodiment of the present application, during the sequential evaporation process, the evaporation rate of the third evaporation source is The evaporation rate of the fourth evaporation source is The evaporation rate of the fifth evaporation source is
[0014] According to an embodiment of the present application, the evaporation thickness of the third evaporation source is 150-250 nm, the evaporation thickness of the fourth evaporation source is 30-50 nm, and the evaporation thickness of the fifth evaporation source is 0.1-2 nm.
[0015] According to an embodiment of the present application, the second evaporation source includes at least one of formamidine iodide, formamidine bromide, formamidine chloride, methylamine iodide, methylamine bromide, methylamine chloride, formamidine acetate and dimethylammonium iodide.
[0016] According to an embodiment of the present application, the evaporation rate of the second evaporation source is
[0017] According to an embodiment of the present application, the thickness of the skeleton layer is 200-300 nm.
[0018] According to an embodiment of the present application, the thickness of the organic layer is 200-300 nm.
[0019] According to an embodiment of the present application, the thickness of the perovskite film is 400-600 nm.
[0020] According to an embodiment of the present application, the annealing process includes a first annealing process and a second annealing process.
[0021] According to an embodiment of the present application, the first annealing process is performed under vacuum conditions.
[0022] According to an embodiment of the present application, the temperature of the first annealing treatment is 100-120° C., and the time is 5-10 min.
[0023] According to an embodiment of the present application, the second annealing process is performed under a humidity condition of 30-40%.
[0024] According to an embodiment of the present application, the temperature of the second annealing treatment is 150-200° C., and the time is 10-30 minutes.
[0025] In the second aspect of the present application, the present application proposes a perovskite film. According to the embodiment of the present application, it is prepared by the method described in the first aspect. As mentioned above, the present application uses aminoethanesulfonic acid as an evaporation source to prepare the perovskite film, which can effectively repair the defects inside the perovskite film, thereby significantly improving the quality of the film. Therefore, the quality of the perovskite film prepared by the method described in the present application is not only improved, but also the open circuit voltage and fill factor of the perovskite solar cell can be improved, further improving the photoelectric conversion efficiency of the battery.
[0026] In the third aspect of the present application, the present application proposes a perovskite solar cell. According to an embodiment of the present application, the perovskite solar cell includes: a substrate; a first charge transport layer, the first charge transport layer is arranged on one side of the substrate; a perovskite absorption layer, the perovskite absorption layer includes the perovskite film described in the second aspect, the perovskite absorption layer is arranged on the side of the first charge transport layer away from the substrate; a second charge transport layer, the second charge transport layer is arranged on the side of the perovskite absorption layer away from the first charge transport layer; an electrode layer, the electrode layer is arranged on the side of the second charge transport layer away from the perovskite absorption layer. Therefore, by means of a method of repairing internal defects of the perovskite film by adding aminoethanesulfonic acid, the prepared perovskite solar cell exhibits significantly improved open circuit voltage and fill factor, thereby achieving higher photoelectric conversion efficiency.
[0027] According to an embodiment of the present application, the perovskite solar cell further includes: a buffer layer, wherein the buffer layer is disposed between the second charge transport layer and the electrode layer.
[0028] In the fourth aspect of the present application, the present application proposes a perovskite tandem cell. According to an embodiment of the present application, the perovskite tandem cell comprises: a top cell and a bottom cell, the top cell is the perovskite solar cell described in the third aspect, and the top cell is arranged on the upper surface of the bottom cell. Therefore, the advantages of the perovskite solar cell of the present application can also be reflected in the perovskite tandem cell, including excellent open circuit voltage, fill factor and photoelectric conversion efficiency.
[0029] In a fifth aspect of the present application, the present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes the perovskite solar cell described in the third aspect or the perovskite tandem cell described in the fourth aspect.
[0030] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0032] Figure 1 is a flow chart of perovskite film preparation according to an embodiment of the present application;
[0033] Figure 2 is a schematic diagram of a first evaporation process according to an embodiment of the present application;
[0034] Figure 3 is a schematic diagram of a second evaporation process according to an embodiment of the present application;
[0035] Figure 4 is a schematic structural diagram of a perovskite film according to an embodiment of the present application;
[0036] Figure 5 is a schematic structural diagram of a titanium ore solar cell according to an embodiment of the present application;
[0037] Figure 6 is a schematic structural diagram of a titanite solar cell containing a buffer layer according to an embodiment of the present application;
[0038] Figure numerals: 01: solid substrate; 02: evaporation source; 03: skeleton layer; 04: skeleton layer; 05: organic layer; 001: substrate; 002: first charge transport layer; 003: perovskite absorption layer; 004: second charge transport layer; 005: electrode layer; 006: buffer layer. DETAILED DESCRIPTION
[0039] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0041] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0043] In this document, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0044] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] Method for preparing perovskite thin film
[0048] In one aspect of the present application, the present application provides a method for preparing a perovskite film. According to an embodiment of the present application, referring to the attached Figure 1 , the method comprising:
[0049] S100: First evaporation process
[0050] In this step, if Figure 2 As shown, a first evaporation treatment is performed on a first evaporation source 02 below a solid substrate 01 to form a skeleton layer on the lower surface of the solid substrate 01 , wherein the first evaporation source 02 includes aminoethanesulfonic acid.
[0051] By adding aminoethanesulfonic acid to the evaporation source during the preparation of perovskite films, the defects inside the perovskite film can be effectively repaired, thereby significantly improving the quality of the film. This improvement not only improves the open circuit voltage and fill factor of perovskite solar cells, but also further improves the photoelectric conversion efficiency of the cell. In addition, this method also helps to achieve uniform manufacturing of large-area perovskite solar cells.
[0052] The specific type of the solid-state substrate is not particularly limited, and a commonly used conductive glass substrate or velvet substrate, or an electron transport layer or hole transport layer of a perovskite solar cell precursor may be used. The conductive glass may be, for example, ITO conductive glass, FTO conductive glass, etc., and the velvet substrate may be, for example, a crystalline silicon velvet substrate of a perovskite-silicon tandem solar cell and other velvet substrates.
[0053] In some embodiments of the present application, the first evaporation source includes a third evaporation source ( Figure 2 1) The fourth evaporation source ( Figure 2 2) and the fifth evaporation source ( Figure 23), the fifth evaporation source includes aminoethanesulfonic acid (AESA). The third evaporation source includes lead iodide (PbI2), and the fourth evaporation source includes at least one of cesium bromide (CsBr) and cesium iodide (CsI). Therefore, the quality of the prepared perovskite film can be improved, and the photoelectric conversion efficiency of the perovskite solar cell can be further improved.
[0054] In some embodiments of the present application, the first evaporation treatment includes co-evaporation treatment or sequential evaporation treatment of the first evaporation source. Among them, co-evaporation treatment refers to evaporating aminoethanesulfonic acid and other evaporation sources at the same time, and sequential evaporation treatment refers to evaporating other evaporation sources except aminoethanesulfonic acid first, and then evaporating aminoethanesulfonic acid after evaporation. Whether it is co-evaporation of aminoethanesulfonic acid or post-evaporation of aminoethanesulfonic acid, it can effectively repair the defects inside the perovskite film and significantly improve the quality of the film.
[0055] In some embodiments of the present application, the evaporation source is subjected to a sequential evaporation treatment, and the sequential evaporation treatment includes: performing a third evaporation treatment on the third evaporation source and the fourth evaporation source; and performing a fourth evaporation treatment on the fifth evaporation source. During the sequential evaporation treatment, the third evaporation source and the fourth evaporation source are evaporated simultaneously first, and then the fifth evaporation source (including aminoethanesulfonic acid) is evaporated. Compared with the co-evaporation treatment, the sequential evaporation treatment can better repair the defects inside the perovskite film, thereby improving the quality of the perovskite film, further improving the open circuit voltage and fill factor of the perovskite solar cell more significantly, and the photoelectric conversion efficiency becomes higher.
[0056] In some embodiments of the present application, during the co-evaporation process, the evaporation rate of the third evaporation source is The evaporation rate of the fourth evaporation source is The evaporation rate of the fifth evaporation source is
[0057] As an example, during the co-evaporation process, the evaporation rate of the third evaporation source may be
[0058] As an example, during the co-evaporation process, the evaporation rate of the fourth evaporation source may be
[0059] As an example, during the co-evaporation process, the evaporation rate of the fifth evaporation source may be
[0060] In some embodiments of the present application, during the evaporation process, the evaporation rate of the third evaporation source is The evaporation rate of the fourth evaporation source is The evaporation rate of the fifth evaporation source is
[0061] As an example, during the downstream evaporation process, the evaporation rate of the third evaporation source may be
[0062] As an example, during the downstream evaporation process, the evaporation rate of the fourth evaporation source may be
[0063] As an example, during the downstream evaporation process, the evaporation rate of the fifth evaporation source may be
[0064] In some embodiments of the present application, the evaporation thickness of the third evaporation source is 150-250 nm, the evaporation thickness of the fourth evaporation source is 30-50 nm, and the evaporation thickness of the fifth evaporation source is 0.1-2 nm.
[0065] It should be noted that the "evaporation thickness" mentioned in the present application refers to the thickness accumulated by the evaporation source on the lower surface of the solid substrate after evaporation using the evaporation source. For example, the evaporation thickness of the fourth evaporation source is 30 to 50 nm, which means that after the fourth evaporation source evaporates, the thickness accumulated by the fourth evaporation source on the lower surface of the solid substrate is 30 to 50 nm.
[0066] As an example, the thickness of the third evaporation source formed below the solid substrate is 180-220 nm, specifically, 180 nm, 185 nm, 190 nm, 195 nm, 200 nm, 205 nm, 210 nm, 215 nm, or 220 nm.
[0067] As an example, the thickness of the fourth evaporation source formed below the solid substrate is 30 to 50 nm, specifically, 30 nm, 32 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 47 nm, 49 nm, and 50 nm.
[0068] As an example, the thickness of the fifth evaporation source formed below the solid substrate is 0.5-1.5 nm, specifically, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, or 1.5 nm.
[0069] S200: Second evaporation process
[0070] In this step, if Figure 3 As shown, a second evaporation process is performed on a second evaporation source below the skeleton layer 03 so as to form an organic layer on the lower surface of the skeleton layer.
[0071] In some embodiments of the present application, the second evaporation source includes at least one of formamidine iodide (FAI), formamidine bromide (FABr), formamidine chloride (FACl), methylamine iodide (MAI), methylamine bromide (MABr), methylamine chloride (MACl), formamidine acetate and dimethylammonium iodide. Therefore, an organic layer can be formed on the lower surface of the skeleton layer, thereby retaining the excellent processability and optoelectronic functionality of the organic material.
[0072] In some embodiments of the present application, the evaporation rate of the second evaporation source is
[0073] As an example, the evaporation rate of the second evaporation source may be
[0074] In some embodiments of the present application, the thickness of the skeleton layer is 200-300 nm. The thickness of the skeleton layer is the sum of the evaporation thickness of the third evaporation source, the evaporation thickness of the fourth evaporation source, and the evaporation thickness of the fifth evaporation source.
[0075] As an example, the thickness of the skeleton layer can be 200nm, 205nm, 210nm, 215nm, 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, 250nm, 255nm, 260nm, 265nm, 270nm, 275nm, 280nm, 285nm, 290nm, 295nm, or 300nm.
[0076] In some embodiments of the present application, the thickness of the organic layer is 200-300 nm. The thickness of the organic layer refers to the thickness accumulated by the second evaporation source on the lower surface of the skeleton layer after evaporation using the second evaporation source.
[0077] As an example, the thickness of the organic layer can be 200nm, 205nm, 210nm, 215nm, 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, 250nm, 255nm, 260nm, 265nm, 270nm, 275nm, 280nm, 285nm, 290nm, 295nm, or 300nm.
[0078] In some embodiments of the present application, the thickness of the perovskite film is 400-600 nm. The thickness of the perovskite film refers to the sum of the thickness of the skeleton layer and the thickness of the organic layer.
[0079] As an example, the thickness of the perovskite film can be 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm, 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, and 600nm.
[0080] S300: Annealing
[0081] In this step, the skeleton layer and the organic layer are annealed to obtain the perovskite film.
[0082] In some embodiments of the present application, the annealing treatment includes a first annealing treatment and a second annealing treatment. Through the two-step annealing treatment, the growth of perovskite crystals can be promoted, defects and impurities inside the crystals can be reduced, the crystal quality and photoelectric properties of the film can be improved, and the quality and performance of the perovskite film can be improved.
[0083] In some embodiments of the present application, the first annealing treatment is performed under vacuum conditions. The vacuum atmosphere is nitrogen. Therefore, it helps to protect the perovskite film from oxidation or other chemical reactions.
[0084] In some embodiments of the present application, the temperature of the first annealing treatment is 100-120° C., and the time is 5-10 min.
[0085] As an example, the temperature of the first annealing treatment may be 100°C, 103°C, 105°C, 108°C, 110°C, 113°C, 115°C, 118°C, or 120°C.
[0086] As an example, the time of the first annealing treatment can be 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min.
[0087] In some embodiments of the present application, the second annealing treatment is performed under the condition of 30-40% humidity, and the protective atmosphere is air. Because formamidine iodide (FAI) has a high solubility in water, the water molecules in the humid air atmosphere can ionize FAI, promote the diffusion of FAI in the inorganic layer, and help improve the quality of the perovskite film.
[0088] As an example, the humidity of the second annealing process may be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40%.
[0089] In some embodiments of the present application, the temperature of the second annealing treatment is 150-200° C., and the time is 10-30 min.
[0090] As an example, the temperature of the first annealing treatment may be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, or 200°C.
[0091] As an example, the time of the first annealing treatment can be 10 min, 13 min, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min, or 30 min.
[0092] Perovskite thin film
[0093] The present application proposes a perovskite film, which is prepared by the aforementioned method. Therefore, the perovskite film prepared by the method described in the present application can effectively repair internal defects, and the quality of the film is significantly improved. At the same time, the open circuit voltage and fill factor of the perovskite solar cell can be improved, further improving the photoelectric conversion efficiency of the cell.
[0094] As an example, refer to Figure 4 The perovskite film includes the skeleton layer 04 and the organic layer 05 , and the organic layer 05 is disposed on at least a portion of the lower surface of the skeleton layer 04 .
[0095] Perovskite solar cells
[0096] The present application proposes a perovskite solar cell. According to an embodiment of the present application, referring to Figure 5 , the perovskite solar cell comprises:
[0097] Base 001;
[0098] A first charge transport layer 002, wherein the first charge transport layer 002 is disposed on one side of the substrate 001;
[0099] A perovskite absorption layer 003, wherein the perovskite absorption layer 003 comprises the aforementioned perovskite film, and the perovskite absorption layer 003 is arranged on a side of the first charge transport layer 002 away from the substrate 001;
[0100] A second charge transport layer 004, wherein the second charge transport layer 004 is disposed on a side of the perovskite absorption layer 003 away from the first charge transport layer 002;
[0101] The electrode layer 005 is arranged on a side of the second charge transport layer 004 away from the perovskite absorption layer 003 .
[0102] As mentioned above, the quality of the perovskite film prepared by the method of the present application is significantly improved. Therefore, the perovskite solar cell based on this quality improvement exhibits higher open circuit voltage, fill factor and photoelectric conversion efficiency.
[0103] In some embodiments of the present application, the first charge transport layer is an electron transport layer, and the second charge transport layer is a hole transport layer.
[0104] In some embodiments of the present application, the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer.
[0105] In some embodiments of the present application, reference Figure 6 The perovskite solar cell further includes a buffer layer 006, which is arranged between the second charge transport layer and the electrode layer.
[0106] In some embodiments of the present application, the buffer layer is disposed between the second charge transport layer and the electrode layer. When the second charge transport layer is a hole transport layer, the buffer layer can form an energy level gradient on the hole transport path to promote hole transport; the wide bandgap buffer layer material can also effectively inhibit the migration of electrons toward the anode, passivate the defect state of the interface, reduce carrier recombination, inhibit the migration of metal ions, and protect the perovskite absorption layer. When the second charge transport layer is an electron transport layer, the main function of the buffer layer is to form an energy level gradient on the electron transport path to promote electron transport; inhibit the migration of metal ions and protect the perovskite absorption layer.
[0107] In some embodiments of the present application, the substrate may be a commonly used conductive glass substrate or a velvet substrate. The conductive glass may be, for example, ITO conductive glass, FTO conductive glass, etc., and the velvet substrate may be, for example, a crystalline silicon velvet substrate of a perovskite-silicon tandem solar cell and other velvet substrates.
[0108] In some embodiments of the present application, the hole transport layer includes nickel oxide containing trivalent nickel ions, wherein nickel oxide is generally expressed as NiOx, which can represent a compound containing oxygen and nickel, and can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating and the like. The preferred thickness of the hole transport layer is 10 to 40 nm.
[0109] In some embodiments of the present application, the hole transport further includes a self-assembled monomolecular material, which is deposited on the surface of the nickel oxide to form a self-assembled monolayer (SAM). The self-assembled monomolecular material can be deposited on the surface of the nickel oxide by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating, etc., with a preferred thickness of 30 to 50 nm.
[0110] In some embodiments of the present application, NiO, Ni(OH)2, Ni2O3, NiOOH and other substances may be present in the hole transport layer.
[0111] In some embodiments of the present application, in the hole transport layer, trivalent nickel ions generally exist in the form of Ni2O3, NiOOH, etc., and divalent nickel ions generally exist in the form of NiO, Ni(OH)2, etc.
[0112] In some embodiments of the present application, the self-assembled monomolecular material includes (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphine (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz) and the like.
[0113] In some embodiments of the present application, the components of the electron transport layer may be electron transport materials commonly used in the art, including but not limited to [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM), [6,6]-phenyl-C 71 -Methyl butyrate (PC 71 BM), fullerene C 60 , Fullerene C 70 , at least one of tin dioxide and zinc oxide, can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating and the like. The preferred thickness of the electron transport layer is 10 to 40 nm.
[0114] In some embodiments of the present application, the material of the buffer layer includes one of bathocuproin (BCP) or tin dioxide (SnO2), and can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating, etc. The preferred thickness of the buffer layer is 1 to 10 nm.
[0115] In some embodiments of the present application, a passivation layer may exist between the perovskite absorption layer and the electron transport layer to passivate defects on the interface between the two.
[0116] In some embodiments of the present application, a passivation layer may exist between the electron transport layer and the electrode layer to improve the performance of the perovskite cell.
[0117] In some embodiments of the present application, the electrode layer is a metal electrode or a transparent electrode. The metal electrode may be, for example, a silver electrode (Ag), a copper electrode (Cu), a gold electrode (Au), an aluminum electrode (Al), a molybdenum electrode (Mo), or a chromium electrode (Cr); the transparent electrode may be, for example, tin-doped indium oxide (ITO), indium zinc oxide (IZO), tungsten-doped indium oxide (IWO), aluminum-doped zinc oxide (AZO), fluorine-doped tin oxide (FTO), zinc oxide, etc. The electrode layer may be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating, etc., and the preferred thickness of the electrode layer is 70 to 130 nm.
[0118] Perovskite tandem battery
[0119] The present application proposes a perovskite tandem cell. According to an embodiment of the present application, the perovskite tandem cell comprises: a top cell and a bottom cell, the top cell is the aforementioned perovskite solar cell, and the top cell is arranged on the upper surface of the bottom cell.
[0120] In some embodiments of the present application, the perovskite tandem cell can be selected from any one of a perovskite / crystalline silicon tandem cell, a full perovskite tandem cell, a perovskite / organic tandem cell, and a perovskite / CIGS tandem cell.
[0121] Electrical equipment
[0122] The present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes the aforementioned perovskite solar cell or the aforementioned perovskite stacked cell. Therefore, the electrical device has all the advantages of the perovskite solar cell, which will not be described in detail here.
[0123] Specifically, electrical equipment may include lighting elements, display elements, mobile devices, etc., and may specifically include street lights, signal indicators, insect killer lamps, electric fans, electric toys, electric tools, battery vehicles, electric vehicles, ships, spacecraft, etc., among which electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft may include airplanes, rockets, space shuttles and spacecraft, etc.; photovoltaic power generation systems may include large-scale ground photovoltaic power generation systems, distributed photovoltaic power generation and building integrated photovoltaic power generation systems, etc.
[0124] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0125] Example 1
[0126] This embodiment provides a method for preparing a perovskite solar cell, comprising the following steps:
[0127] (1) NiOx was deposited on a transparent conductive substrate by magnetron sputtering with a thickness of 25 nm;
[0128] (2) The self-assembled material Me-4PACz was deposited on the NiOx surface by spin coating. Me-4PACz was dissolved in ethanol at a concentration of 0.5 mg / mL. The spin coating speed was 3000 rpm / s. The material was annealed at 100°C for 10 min to form a SAM layer with a thickness of 30 to 50 nm.
[0129] (3) PbI2, CsBr and AESA are co-evaporated on the surface of the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm and the AESA evaporation rate is The thickness is 0.9nm.
[0130] (4) Depositing an organic layer on the surface of the skeleton layer by evaporation, wherein the evaporation source of the organic layer is selected from formamidine iodide, and the evaporation rate is The thickness is 220 nm, and the prefabricated perovskite layer is obtained;
[0131] (5) The prefabricated perovskite layer is subjected to a step-by-step annealing treatment, wherein the annealing is first carried out in a glove box, where the atmosphere in the glove box is nitrogen, the annealing temperature is 100° C., and the annealing time is 10 min. Thereafter, the annealing is carried out in an air atmosphere with a humidity of 30-40%, the annealing temperature is 150° C., and the annealing time is 20 min to obtain the perovskite layer.
[0132] (6) Using the evaporation method to evaporate a 20nm electron transport layer C on the surface of the perovskite layer 60 , evaporation rate and 5nm buffer layer BCP, the evaporation rate is
[0133] (7) The Ag metal electrode layer was prepared by evaporation method, and the evaporation rate of Ag was The thickness is 100nm, and the battery preparation is completed.
[0134] Example 2
[0135] The preparation method of Example 2 is substantially the same as that of Example 1, except that in step (3):
[0136] Step (3) PbI2, CsBr and AESA are co-evaporated on the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm and the AESA evaporation rate is The thickness is 0.9nm.
[0137] Example 3
[0138] The preparation method of Example 3 is substantially the same as that of Example 1, except that in step (3):
[0139] Step (3) PbI2, CsBr and AESA are co-evaporated on the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm and the AESA evaporation rate is The thickness is 0.9nm.
[0140] Example 4
[0141] The preparation method of Example 4 is substantially the same as that of Example 1, except that in step (3):
[0142] Step (3) PbI2, CsBr and AESA are co-evaporated on the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm and the AESA evaporation rate is Thickness: 0.9nm
[0143] Example 5
[0144] The preparation method of Example 5 is substantially the same as that of Example 1, except that in step (3):
[0145] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 1.5nm.
[0146] Example 6
[0147] The preparation method of Example 6 is substantially the same as that of Example 5, except that in step (3):
[0148] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 1.5nm.
[0149] Example 7
[0150] The preparation method of Example 7 is substantially the same as that of Example 5, except that in step (3):
[0151] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 1.5nm.
[0152] Example 8
[0153] The preparation method of Example 8 is substantially the same as that of Example 5, except that in step (3):
[0154] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 1.5nm.
[0155] Example 9
[0156] The preparation method of Example 9 is substantially the same as that of Example 5, except that in step (3):
[0157] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 2nm.
[0158] Example 10
[0159] The preparation method of Example 10 is substantially the same as that of Example 5, except that in step (3):
[0160] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 0.5nm.
[0161] Embodiment 11
[0162] The preparation method of Example 11 is substantially the same as that of Example 5, except that in step (3):
[0163] Step (3) uses an evaporation method to evaporate PbI2 and CsBr on the surface of the SAM layer at the same time, and then evaporates the AESA layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm; the AESA evaporation rate is The thickness is 3nm.
[0164] Example 12
[0165] The preparation method of Example 12 is basically the same as the preparation method of Example 1, except that step (1), step (3) and step (4) are as follows:
[0166] In step (1), NiOx is deposited on a transparent conductive substrate on a silicon bottom cell by magnetron sputtering with a thickness of 25 nm;
[0167] In step (3), PbI2, CsBr and AESA are co-evaporated on the surface of the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 220nm and the CsBr evaporation rate is The thickness is 44nm and the AESA evaporation rate is Thickness: 1.1nm;
[0168] In step (4), an organic layer is deposited on the surface of the skeleton layer by evaporation, and the evaporation source of the organic layer is selected from formamidine iodide, and the evaporation rate is The thickness is 270nm, and a prefabricated perovskite layer is obtained.
[0169] Example 13
[0170] The preparation method of Example 13 is substantially the same as that of Example 12, except for step (3):
[0171] In step (3), PbI2 and CsBr are evaporated simultaneously on the surface of the SAM layer by evaporation method, and then the AESA layer is evaporated. The evaporation rate of PbI2 is The thickness is 220nm and the CsBr evaporation rate is The thickness is 44nm; the AESA evaporation rate is The thickness is 1.5nm.
[0172] Comparative Example 1
[0173] This comparative example provides a method for preparing a perovskite solar cell. The difference between comparative example 1 and embodiment 1 is that the evaporation source AESA is not used in comparative example 1, and specifically comprises the following steps:
[0174] (1) NiOx was deposited on a transparent conductive substrate by magnetron sputtering with a thickness of 25 nm;
[0175] (2) The self-assembled material Me-4PACz was deposited on the NiOx surface by spin coating. Me-4PACz was dissolved in ethanol at a concentration of 0.5 mg / mL. The spin coating speed was 3000 rpm / s and annealed at 100°C for 10 min to form a SAM layer with a thickness of 30 to 50 nm. ;
[0176] (3) PbI2 and CsBr are co-evaporated on the surface of the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 180nm and the CsBr evaporation rate is The thickness is 36nm.
[0177] (4) Depositing an organic layer on the surface of the skeleton layer by evaporation, wherein the evaporation source of the organic layer is selected from formamidine iodide, and the evaporation rate is The thickness is 220 nm, and the prefabricated perovskite layer is obtained;
[0178] (5) The prefabricated perovskite layer is subjected to a step-by-step annealing treatment, wherein the annealing is first carried out in a glove box, where the atmosphere in the glove box is nitrogen, the annealing temperature is 100° C., and the annealing time is 10 min. Thereafter, the annealing is carried out in an air atmosphere with a humidity of 30-40%, the annealing temperature is 150° C., and the annealing time is 20 min to obtain the perovskite layer.
[0179] (6) Using the evaporation method to evaporate a 20nm electron transport layer C on the surface of the perovskite layer 60 , evaporation rate and 5nm buffer layer BCP, the evaporation rate is
[0180] (7) The Ag metal electrode layer was prepared by evaporation method, and the evaporation rate of Ag was The thickness is 100nm, and the battery preparation is completed.
[0181] Comparative Example 2
[0182] The preparation method of Comparative Example 2 is substantially the same as that of Example 12. The difference between Comparative Example 2 and Example 12 is that the evaporation source AESA is not used in Comparative Example 2. The difference is step (3), which is specifically:
[0183] In step (3), PbI2 and CsBr are co-evaporated on the surface of the SAM layer by evaporation to form a skeleton layer. The evaporation rate of PbI2 is The thickness is 220nm and the CsBr evaporation rate is The thickness is 44nm.
[0184] The open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE) of the solar cells of Examples 1 to 13 and Comparative Examples 1 to 2 were tested respectively, and the test results are shown in Tables 1 and 2. The results of Examples 1 to 11 relative to Comparative Example 1 show that, compared with the case where the evaporation source aminoethanesulfonic acid is not used, the perovskite film prepared using aminoethanesulfonic acid can significantly improve the fill factor and photoelectric conversion efficiency of the single-junction perovskite solar cell.
[0185] The results of Examples 12 and 13 relative to Comparative Example 2 show that, compared with the case where aminoethanesulfonic acid is not used as an evaporation source, the perovskite film prepared using aminoethanesulfonic acid can significantly improve the filling factor and photoelectric conversion efficiency of the perovskite-silicon tandem solar cell.
[0186] The results of Examples 1, 2, 3, 5, 6, 7, 9, 10, 12 and 13 show that when evaporating aminoethanesulfonic acid during co-evaporation and sequential evaporation, selecting a suitable evaporation rate and evaporation thickness has a significant effect on improving the photoelectric conversion efficiency of single-junction perovskite solar cells and perovskite-silicon tandem solar cells.
[0187] Table 1 Comparison of photovoltaic parameters of single-junction perovskite solar cells using different evaporation methods
[0188]
[0189]
[0190] Table 2 Comparison of photovoltaic parameters of perovskite-silicon tandem solar cells using different evaporation methods
[0191] Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Example 12 1.81 17.95 74.04 24.02 Example 13 1.82 17.63 73.21 23.48 Comparative Example 2 1.71 18.08 67.75 20.94
[0192] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0193] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a perovskite film, characterized in that: include: Performing a first evaporation treatment on a first evaporation source below the solid substrate to form a skeleton layer on the lower surface of the solid substrate, wherein the first evaporation source includes aminoethanesulfonic acid; Performing a second evaporation process on a second evaporation source below the skeleton layer so as to form an organic layer on the lower surface of the skeleton layer; The skeleton layer and the organic layer are annealed to obtain the perovskite film.
2. The method according to claim 1, characterized in that The first evaporation source includes a third evaporation source, a fourth evaporation source, and a fifth evaporation source, and the fifth evaporation source includes the aminoethanesulfonic acid.
3. The method according to claim 2, characterized in that The first evaporation treatment includes performing a co-evaporation treatment or a sequential evaporation treatment on the first evaporation source.
4. The method according to claim 3, characterized in that The first evaporation source is subjected to a downstream evaporation treatment, wherein the downstream evaporation treatment comprises: performing a third evaporation process on the third evaporation source and the fourth evaporation source; and The fifth evaporation source is subjected to a fourth evaporation process.
5. The method according to claim 4, characterized in that The third evaporation source includes lead iodide; And / or, the fourth evaporation source includes at least one of cesium bromide and cesium iodide.
6. The method according to claim 3, characterized in that During the co-evaporation process, the evaporation rate of the third evaporation source is The evaporation rate of the fourth evaporation source is The evaporation rate of the fifth evaporation source is 7. The method according to claim 3, characterized in that During the downstream evaporation process, the evaporation rate of the third evaporation source is The evaporation rate of the fourth evaporation source is The evaporation rate of the fifth evaporation source is 8. The method according to claim 3, characterized in that The evaporation thickness of the first evaporation source is 150-250 nm, the evaporation thickness of the second evaporation source is 30-50 nm, and the evaporation thickness of the third evaporation source is 0.1-2 nm.
9. The method according to claim 1, characterized in that: The second evaporation source includes at least one of formamidine iodide, formamidine bromide, formamidine chloride, methylamine iodide, methylamine bromide, methylamine chloride, formamidine acetate and dimethylammonium iodide; And / or, the evaporation rate of the second evaporation source is 10. The method according to claim 1, characterized in that The thickness of the skeleton layer is 200 to 300 nm; And / or, the thickness of the organic layer is 200 to 300 nm; And / or, the thickness of the perovskite film is 400-600 nm.
11. The method according to claim 1, characterized in that The annealing process includes a first annealing process and a second annealing process.
12. The method according to claim 11, wherein the first annealing process is performed under vacuum conditions; And / or, the temperature of the first annealing treatment is 100-120° C., and the time is 5-10 min; And / or, the second annealing treatment is performed under a humidity condition of 30-40%; And / or, the temperature of the second annealing treatment is 150-200° C., and the time is 10-30 min.
13. A perovskite film, characterized in that: The method is used to prepare the product according to any one of claims 1 to 12.
14. A perovskite solar cell, characterized in that: include: substrate; a first charge transport layer, wherein the first charge transport layer is disposed on one side of the substrate; A perovskite absorption layer, wherein the perovskite absorption layer comprises the perovskite thin film according to claim 11, and the perovskite absorption layer is arranged on a side of the first charge transport layer away from the substrate; a second charge transport layer, wherein the second charge transport layer is arranged on a side of the perovskite absorption layer away from the first charge transport layer; An electrode layer is disposed on a side of the second charge transport layer away from the perovskite absorption layer.
15. The perovskite solar cell according to claim 14, characterized in that: Further including: A buffer layer is provided between the second charge transport layer and the electrode layer.
16. A perovskite tandem battery, comprising: A top cell and a bottom cell, wherein the top cell is the perovskite solar cell according to claim 14 or 15, and the top cell is arranged on the upper surface of the bottom cell.
17. An electrical equipment, characterized in that: include: The perovskite solar cell according to claim 14 or 15 or the perovskite tandem cell according to claim 16.